FY17 Equatorial Guinea Country Opinion Survey Report - World Bank Group (World Bank, Washington, DC, 2018)
The Country Opinion Survey in Equatorial Guinea assists the World Bank Group (WBG) in gaining a better understanding of how stakeholders in Equatorial Guinea perceive the WBG. It provides the WBG with systematic feedback from national and local governments, multilateral/bilateral agencies, media, academia, the private sector, and civil society in Equatorial Guinea on 1) their views regarding the general environment in Equatorial Guinea; 2) their overall attitudes toward the WBG in Equatorial Guinea; 3) overall impressions of the WBG’s effectiveness and results, knowledge work and activities, and communication and information sharing in Equatorial Guinea; and 4) their perceptions of the WBG’s future role in Equatorial Guinea.